2021
DOI: 10.3390/molecules26082282
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Lactone Obtained from Eucalyptus tereticornis Increases Glucose Uptake and Reduces Inflammatory Activity and Intracellular Neutral Fat: An In Vitro Study

Abstract: Obesity has a strong relationship to insulin resistance and diabetes mellitus, a chronic metabolic disease that alters many physiological functions. Naturally derived drugs have aroused great interest in treating obesity, and triterpenoids are natural compounds with multiple biological activities and antidiabetic mechanisms. Here, we evaluated the bioactivity of ursolic acid lactone (UAL), a lesser-known triterpenoid, obtained from Eucalyptus tereticornis. We used different cell lines to show for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The literature attributes significant lipid-lowering effects in HepG2 cells to the many triterpenoids [56], proposing them as functional compounds to improve hepatic stress [57]. These results are, thus, in line with the scientific literature [56][57][58][59][60], and underline the potential of pentacyclic triterpene-rich EXT to lower HG-induced intracellular lipid levels.…”
Section: Effect Of Ext and Me-ext On Intracellular Lipid Accumulation...supporting
confidence: 77%
“…The literature attributes significant lipid-lowering effects in HepG2 cells to the many triterpenoids [56], proposing them as functional compounds to improve hepatic stress [57]. These results are, thus, in line with the scientific literature [56][57][58][59][60], and underline the potential of pentacyclic triterpene-rich EXT to lower HG-induced intracellular lipid levels.…”
Section: Effect Of Ext and Me-ext On Intracellular Lipid Accumulation...supporting
confidence: 77%
“…OBE100 extract has UA, OA, and UAL as the main molecules. These three triterpenoids have been shown to present antioxidant and anti-inflammatory effects [ 12 , 16 , 41 , 42 ]. In this study, the treatment of activated macrophages with the individual triterpenes changed the cells' expression pattern, and this change was increased when we mixed them (M1).…”
Section: Resultsmentioning
confidence: 99%
“…These molecules have various biological properties, including antioxidant and anti-inflammatory activities. It has been shown that UA, OA and UAL reduce oxidative stress and inflammation, blocking the NF-kB activation, inhibiting the expression of proinflammatory genes or reducing the production of reactive oxygen species (ROS) [ [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%
“…In adipogenesis, increased insulin resistance, adipocyte hypertrophy, lipid accumulation and energy demand cause an increase in intracellular oxidative stress ( Gregoire et al, 1998 ). Studies have reported that in the inhibition of preadipocyte differentiation, adipogenesis, lipid accumulation, as well as reduction of cell density, mitosis, and insulin resistance may be important mechanisms in inhibiting of adipocyte hypertrophy ( Deepa et al, 2015 ; Balcazar et al, 2021 ). PTS is a natural phenolic compound found predominantly in blueberries ( Aiyer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%